2005
DOI: 10.1051/0004-6361:20053294
|View full text |Cite
|
Sign up to set email alerts
|

Structural parameters of the hot pulsating B subdwarf Feige 48 from asteroseismology

Abstract: We present observations followed by a thorough analysis of the rapidly pulsating subdwarf B star (or EC 14026 star) Feige 48. This work is part of a long term multifaceted effort to exploit the strong asteroseismological potential of sdB pulsators which involves high sensitivity photometric observations, accurate spectroscopic measurements, and the development of appropriate modelling tools dedicated to the interpretation of the seismic data. Our model atmosphere analysis of the time averaged optical spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 33 publications
5
76
0
Order By: Relevance
“…The case of Feige 48 is different. Both Charpinet et al (2005c) and Van Grootel et al (2008a) used 2G models and the same data set, but with the important difference that Van Grootel et al (2008a) fitted all the nine available frequency components in terms of rotationally-split modes with indices k, l, and m, while Charpinet et al (2005c) fitted only the four frequencies identified a priori as the central m = 0 components of rotationally-split multiplets. While the approach of Van Grootel et al (2008a) is to be preferred as a matter of principle, the rather different value of the derived mass, 0.519 ± 0.009 M versus 0.460 ± 0.008 M , heavily hinges on the reality of the lowamplitude f − 4 and f + 4 components of the f 4 triplet reported in Table 1 of Van Grootel et al (2008a).…”
Section: The Asteroseismological Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The case of Feige 48 is different. Both Charpinet et al (2005c) and Van Grootel et al (2008a) used 2G models and the same data set, but with the important difference that Van Grootel et al (2008a) fitted all the nine available frequency components in terms of rotationally-split modes with indices k, l, and m, while Charpinet et al (2005c) fitted only the four frequencies identified a priori as the central m = 0 components of rotationally-split multiplets. While the approach of Van Grootel et al (2008a) is to be preferred as a matter of principle, the rather different value of the derived mass, 0.519 ± 0.009 M versus 0.460 ± 0.008 M , heavily hinges on the reality of the lowamplitude f − 4 and f + 4 components of the f 4 triplet reported in Table 1 of Van Grootel et al (2008a).…”
Section: The Asteroseismological Samplementioning
confidence: 99%
“…In the light of the still unpublished results of a recent extended observational photometric campaign on Feige 48, we are forced at this stage to question the reality of this "triplet", however. For the present needs, we prefer the earlier estimate of the mass provided by Charpinet et al (2005c), which does not depend on whether or not a f 4 triplet exists in the light curve of Feige 48. Billères & Fontaine (2005) analyzed the p-mode pulsator EC 05217−3914 in the same manner as in the previous studies, but could not find time to produce an error analysis.…”
Section: The Asteroseismological Samplementioning
confidence: 99%
“…This model has been refined subsequently by Charpinet et al (2005b), who exploited a higher quality (white light) data set and found the same mode identification. In both cases, in the search in parameter space for the optimal model, it was explicitly assumed that the observed modes had to belong to degree indices from l ¼ 0 up to and including l ¼ 3.…”
Section: Pg 0014+067 (J05)mentioning
confidence: 92%
“…3 are excited to visible levels in that star. Except for the restriction to l-values from 0 to 3, no a priori constraints were imposed in the asteroseismological exercises carried out by Brassard et al (2001) and Charpinet et al (2005b), and the actual mode identification (the determination of both the radial order k and the degree index l for each observed pulsation) came out as a natural by-product of the method.…”
Section: Pg 0014+067 (J05)mentioning
confidence: 99%
See 1 more Smart Citation